METHODOLOGY FOR DISTRIBUTED DESIGNING OF DISTRIBUTED VIRTUAL INSTRUMENTS - Winiecki, Wieslaw (International Journal of Computing, 2014)
A generic architecture of a networked Distributed Virtual Measurement Instrument (DVI) is presented. General assumptions for distributed design of networked DVI’s are described. The generic architecture of a distributed, networked and platform-independent environment for DVI designing, together with the generic methodology for distributed designing of networked DVI is proposed. Currently employed DVI design methodologies are presented and assessed.